2021
DOI: 10.2147/pgpm.s337695
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Pan-Cancer Analysis of KIF23 and a Prediction Model Based on KIF23 in Clear Cell Renal Cell Carcinoma (ccRCC)

Abstract: Purpose This study aims to carry out a pan-cancer analysis of kinesin family member 23 (KIF23) and construct a predictive model for the prognosis of clear cell renal cell carcinoma (ccRCC) patients. Methods We evaluated the differential expression of KIF23 in pan-cancer by The Cancer Genome Atlas (TCGA) and Oncomine database. Then, the correlation between KIF23 with prognosis, clinical grade, stage, immune subtype, tumor mutation burden (TMB), microsatellite instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, there seldom exists a perfect indicating effect for the genes investigated in the current study. The pan-cancer analysis of KIF23 showed that it had a close correlation with the clinical stage and it was higher along with the higher clinical stage, but the research did not further explore the PFI and other survival index [ 9 ]. At the same time, in the research conducted by the Yun Chen, TGFBI was also elevated in various kinds of cancers (cholangiocarcinoma, colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), GBM, head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and thyroid carcinoma), and it also showed a great value in the survival aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, there seldom exists a perfect indicating effect for the genes investigated in the current study. The pan-cancer analysis of KIF23 showed that it had a close correlation with the clinical stage and it was higher along with the higher clinical stage, but the research did not further explore the PFI and other survival index [ 9 ]. At the same time, in the research conducted by the Yun Chen, TGFBI was also elevated in various kinds of cancers (cholangiocarcinoma, colon adenocarcinoma (COAD), esophageal carcinoma (ESCA), GBM, head and neck squamous cell carcinoma (HNSC), kidney renal clear cell carcinoma (KIRC), kidney renal papillary cell carcinoma (KIRP), liver hepatocellular carcinoma (LIHC), rectum adenocarcinoma (READ), stomach adenocarcinoma (STAD), and thyroid carcinoma), and it also showed a great value in the survival aspects.…”
Section: Discussionmentioning
confidence: 99%
“…It actively participates in the development of the cell membrane during the cell division process. Aberrant expression or activity may result in excessive cell proliferation and is associated with the invasion and migration of tumor cells [29]. KIF23 dysfunction leads to mitotic arrest and the appearance of binucleated or multinucleated cells, which in turn leads to tumorigenesis [30].…”
Section: The Protein Expression Of Ccna2 and Kif23mentioning
confidence: 99%
“…Five FI-DEGs (CCR4, CMTM3, IFITM1, MX2, and NR3C2) could be used as biomarkers to predict the outcome and diagnosis of KIRC in patients [105]. Evidence suggests that KIF23 may have an important role in the onset and progression of many cancers [106]. It can be an effective predictive biomarker in ccRCC, and the nomogram based on KIF23 may help with improved treatment recommendations for ccRCC patients [106].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%
“…Evidence suggests that KIF23 may have an important role in the onset and progression of many cancers [106]. It can be an effective predictive biomarker in ccRCC, and the nomogram based on KIF23 may help with improved treatment recommendations for ccRCC patients [106]. Other studies reported that FDFT1 and acyl-CoA thioesterases 8 and 11 can be used as new biomarkers for ccRCC [107, 108].…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%